European Respiratory Society guideline on long-term management of children with bronchopulmonary dysplasia - (:unkn) unknown (My University, 2020)
This document provides recommendations for monitoring and treatment of children in whom bronchopulmonary dysplasia (BPD) has been established and who have been discharged from the hospital, or who were >36 weeks of postmenstrual age. The guideline was based on predefined Population, Intervention, Comparison and Outcomes (PICO) questions relevant for clinical care, a systematic review of the literature and assessment of the evidence using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. After considering the balance of desirable (benefits) and undesirable (burden, adverse effects) consequences of the intervention, the certainty of the evidence, and values, the task force made conditional recommendations for monitoring and treatment of BPD based on very low to low quality of evidence. We suggest monitoring with lung imaging using ionising radiation in a subgroup only, for example severe BPD or recurrent hospitalisations, and monitoring with lung function in all children. We suggest to give individual advice to parents regarding daycare attendance. With regards to treatment, we suggest the use of bronchodilators in a subgroup only, for example asthma-like symptoms, or reversibility in lung function; no treatment with inhaled or systemic corticosteroids; natural weaning of diuretics by the relative decrease in dose with increasing weight gain if diuretics are started in the neonatal period; and treatment with supplemental oxygen with a saturation target range of 90–95%. A multidisciplinary approach for children with established severe BPD after the neonatal period into adulthood is preferable. These recommendations should be considered until new and urgently needed evidence becomes available.